High-depth spatial transcriptome analysis by photo-isolation chemistry - Mizuki Honda (Nature Portfolio, 2021)
Spatial analysis of RNAseq data is important. Here the authors report a method for transcriptome profiling combined with photo-isolation chemistry to allow determination of expression profiles specifically from photo-irradiated regions of interest which they use in mouse brains and embryonic tissues.